Cooperative Model dan Literasi Hukum Sebagai Perantara Pencegahan Perkawinan Anak Dibawah Umur Melalui Pendekatan Adat Dharma Wacana - Nyoman Tania Nesa; Fadia Ardian Adisty; Agnes Tio Evelyna Debataraja; Muhammad Adymas Hikal Fikri (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Child marriage is a socio-legal issue that persists in various regions, including indigenous communities with strong authority structures and cultural values. This study aims to analyze the effectiveness of the cooperative model and legal literacy as intermediaries in preventing child marriage through the Dharma Wacana customary approach. The cooperative model is used as a collaborative framework that involves traditional leaders, religious leaders, village officials, parents, and adolescents in the process of education and joint decision-making. Meanwhile, legal literacy plays a role in strengthening the community's understanding of the age limit for marriage, child protection, and legal sanctions as stipulated in national legislation. The findings show that the integration of positive legal values with local wisdom through Dharma Wacana is able to create a more inclusive space for dialogue, increase legal awareness, and reduce the legitimacy of child marriage practices based on custom. Thus, the application of the cooperative model and legal literacy through a customary approach not only strengthens the function of law as a means of protection but also reinforces the role of local culture as a strategic partner in preventing child marriage.